El conversacionalismo y la verdad como norma de la aserción. El debate Rorty/Engel - Penelas, Federico (Revista de Filosofía, 2009)
In this work I will analyze the debate between Pascal Engel and Richard Rorty about the relevance of the notion of truth to the characterization of assertion. I will point out the theoretic advantages of Rortian conversationalism’s refuse of the idea of truth as a norm of assertion. For that, first of all, I will make an analysis of Rortian deflationism. Then, I will make an reconstruction of Engel’s defense of the normativity of truth. Finally, I will establish that that defense is overcome by conversationalism. During the discussion I will criticize some theoretical developments by Akeel Bilgrami, Harry Frankfurt and Huw Price which could be useful to Engel’s position.